(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The Early Pleistocene sedimentary succession of the Dandiero (Buia) Basin (Danakil Depression, Eritrea) has preserved a rich paleontological, paleoanthropological, and archeological record. Fieldwork undertaken between 1995 and 2003 on a site at Uadi Aalad (Abbate et al. 1998) led to the discovery of one-million-year-old human remains. They consist of a cranium in excellent preservation condition (UA-31), two permanent teeth (UA-222 and UA-369), and three pelvic portions (UA-173, UA-405 and UA-466, the latter recovered on 2003). The cranium and the postcranial remains represent a single adult individual, likely of female sex. The cranium evidences a blend of "erectus-like" and progressive morpho-architectural features, the latter more commonly found in the Middle Pleistocene. Preparation and restoration of the specimens (notably, of the virtually complete UA-31 face) were only completed on September 2003. The revision, refinement, and integration of our previous analytical and interpretative work (cf. Abbate et al. 1998; Macchiarelli et al. 2002) is in progress within the context of the paleoanthropological reord currently available for the African Early to Middle Pleistocene.